The connection between mechanical and functional indicators in rowing - Gospodarski, N.; Hristov, R. (Department of Water Sports, NSA, 2020)
During arowing practice, therowingergometer training isthemost popular wayto control the specific loads. Byrowing on the ergometer the athletes could achievethe same kinematic characteristics as they do when they rowonwater. The ergometercontainsamicroprocessor unit thatgives informationabout the power produced, the work that the athlete hasdone, the theoretical distance that he/she haspassed, and theenergy that isconsumedduringthe different types ofloadsthat are set. The comparison betweenthe components of the external and internalloads gives the coachesachance to personalize the training and to achieve the best sport`s results for any athlete. In training practice the coaches use a different distance that helps athletes to develop the most important physical and performancecapabilities. At the given study we describe the different distancesandwe alsodefine the capacity on the different energy expenditure systems of the athletes` body.